2007
DOI: 10.1007/s11150-007-9002-5
|View full text |Cite
|
Sign up to set email alerts
|

Does work during childhood affect the health of Guatemalan adults?

Abstract: The diversity of potential relationships between child labor and health makes the empirical disentanglement of the causal relationship a difficult exercise. This paper examines the long run impact of child labour on health by controlling for unobserved household specific characteristics. In order to control for the unobserved households specific effect, we estimate a conditional fixed effect model using data on siblings constructed from the Guatemalan National Survey of Living Condition. The estimation results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The findings of this study are important because they show that, in addition to the detrimental effects of child labor on the health of the children (O'Donnell et al, 2005;Rosati & Straub, 2007) and on their academic achievement (Heady, 2003;Psacharopoulos, 1997), there may also be harmful emotional effects.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The findings of this study are important because they show that, in addition to the detrimental effects of child labor on the health of the children (O'Donnell et al, 2005;Rosati & Straub, 2007) and on their academic achievement (Heady, 2003;Psacharopoulos, 1997), there may also be harmful emotional effects.…”
Section: Discussionmentioning
confidence: 85%
“…Some researchers have addressed the effects of labor on the health of working children (O'Donnell, Rosati, & van Doorslaer, 2005;Rosati & Straub, 2007). Several researchers have also examined issues related to the economic impact of child labor (Jensen & Skyt Nielsen, 1997;Patrinos & Psacharopoulos, 1997), and others have linked this issue with educational achievement, with child labor contributing to lower academic achievement (Heady, 2003;Psacharopoulos, 1997).…”
mentioning
confidence: 99%
“…A lack of effect of the intervention on child's work-related health outcomes might, at least partially, be due to the so-called "healthy worker effect" suggesting that the healthiest persons are most likely to work [3]. Relating "today's health" with "today's work" might miss important health implications that occur after a while: adults who entered the work force when they were children report lower health [37,38]. Therefore, future research looking into long-term impact of child work would be vital.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of child laborers in countries around the world have documented high rates of work-related injuries (Beegle et al, 2009;Dalal et al, 2015;Doocy et al, 2007;Nuwayhid et al, 2005;Tiwari et al, 2004;Wolff and Maliki, 2008); high levels of toxicity (Ide and Parker, 2005;Junaid et al, 2017;Nuwayhid et al, 2005;Sughis et al, 2012); chronic sleep deprivation, malnutrition, exposure to hazardous chemicals and increased risk of injury, as well as verbal, physical or sexual abuse (International Labour Organization, 2007;Matsuno and Blagbrough, 2006;de Silva-de-Alwis, 2008;Zainab and Kadir, 2016); and poor mental health outcomes (Sturrock and Hodes, 2016). Moreover, a number of studies have shown that the health effects of laboring at an early age result in an increase in the likelihood of experiencing poor health outcomes as adults (Kassouf et al, 2001;Nuwayhid et al, 2005;O'Donnell et al, 2005;Rosati and Straub, 2007;Wolff and Maliki, 2008), including having at least one chronic disease and experiencing difficulty with mobility (Akee et al, 2010;Lee and Orazem, 2010;Nishijima et al, 2015).…”
Section: Impact Of Child Labormentioning
confidence: 99%